MANAGING QUALITY ON CONSTRUCTION SITES IN SOUTH AFRICA: AN EASTERN CAPE STUDY - Fidelise EMUZE; Christopher MHLWA (Journal of Construction Project Management and Innovation)
In South Africa, construction projects still experience non- conformance to quality requirements as well as cost and schedule overruns to the detriment of clients. For project success to be attained, conformance to these parameters is the minimum expectation in the face of other considerations related to client satisfaction. Thus, through the use of existing literature, and a fie ld study conducted among site management employees working for general contractors (GCs) in the Eastern Cape province of South Africa, the management of quality on construction sites was examined. The study that was descriptive in nature shows that lack of skilled general workers and artisans contribute to poor quality control and management processes; while defects and rework form the main reason for project quality deviations on the sampled sites. The quality deviations in turn influence the level of cost and time overrun experienced on construction projects. The study corroborates the literature reviewed in that there is an interrelationship between cost, quality, and time in South African construction. For example, when the quality of work is below the r equired threshold, it leads to cost and time overruns due to rework that requires extra effort and expense. The value of this explorative study is that both site management and workers should be hands on in terms of managing quality on project sites as fai lure to do so could have a domino effect relative to other project considerations.